Islamic Tourism Development Strategy: Integrating Local Wisdom and Digital Innovation - Marlizar, Marlizar; Lastri, Surna; Erlinda, Erlinda (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2025)
With its rich cultural heritage and strong religious identity, Aceh Province, Indonesia, has a strategic opportunity for Islamic tourism development. Combining local wisdom and digitalization can create distinctive experiences, boosting visitor numbers and improving community income and welfare. However, significant challenges persist, including limited attraction diversification, inadequate human resources, minimal digital promotion, and insufficient government support and stakeholder coordination. This study aims to formulate a strategic framework for the development of Islamic tourism destinations in Banda Aceh City by integrating local wisdom and digital technologies to enhance community income. Employing a qualitative approach, the study conducted in-depth interviews with nine key informants, including government officials, tourism practitioners, and business actors. The data were analyzed using NVivo 15 software. The results reveal that tourism in Banda Aceh suffers from a lack of innovation, low human resource competence, and the absence of regulatory instruments such as the Regional Tourism Development Master Plan (RIPPARDA) and halal certification. The proposed strategies include collaborative RIPPARDA development, targeted human resource capacity-building, digital marketing, local wisdom-based festival creation, and enhanced policy and stakeholder support. These findings underscore the need for integrated, cross-sector efforts to optimize the potential of halal tourism in supporting inclusive local economic development.========================================================================================================ABSTRAK – Strategi Pengembangan Pariwisata Syariah: Integrasi Kearifan Lokal dan Inovasi Digital. Dengan kekayaan warisan budaya dan identitas keagamaannya yang kuat, Aceh memiliki peluang besar untuk pengembangan pariwisata syariah. Penggabungkan kearifan lokal dengan digitalisasi dapat menciptakan pengalaman unik wisatawan, meningkatkan jumlah pengunjung, serta memperbaiki pendapatan dan kesejahteraan masyarakat. Namun dalam implementasinya terdapat sejumlah tantangan seperti kurangnya diversifikasi daya tarik wisata, rendahnya kapasitas sumber daya manusia, minimnya promosi digital, serta kurangnya dukungan pemerintah dan sinergi antar pemangku kepentingan. Penelitian ini bertujuan untuk merumuskan strategi pengembangan destinasi pariwisata Islam berbasis kearifan lokal dan teknologi digital untuk meningkatkan pendapatan masyarakat di Kota Banda Aceh. Penelitian ini menggunakan pendekatan kualitatif dengan melakukan wawancara mendalam terhadap sembilan informan kunci yang terdiri dari praktisi, pejabat pemerintah, dan pelaku usaha pariwisata yang kemudian dianalisis dengan software NVivo 15. Hasil penelitian menunjukkan bahwa pariwisata di Banda Aceh masih cenderung monoton, sumber daya manusia belum kompeten, serta belum adanya regulasi spesifik seperti Rencana Induk Pengembangan Pariwisata Daerah (RIPPARDA) dan sertifikasi halal. Strategi yang disarankan meliputi penyusunan RIPPARDA secara kolaboratif, penguatan kapasitas sumber daya manusia, promosi digital, pengembangan festival berbasis kearifan lokal, serta dukungan kebijakan dan kerja sama antar pemangku kepentingan. Temuan ini menekankan pentingnya upaya lintas sektor yang terintegrasi untuk mengoptimalkan potensi pariwisata halal dalam mendorong pembangunan ekonomi lokal yang inklusif.